How Russia really works : the informal practices that shaped post-Soviet politics and business - Ledeneva, Alena V., 1964- (Culture and society after socialism., 2006)
During the Soviet era, blat-the use of personal networks for obtaining goods and services in short supply and for circumventing formal procedures-was necessary to compensate for the inefficiencies of socialism. The collapse of the Soviet Union produced a new generation of informal practices. In How Russia Really Works, Alena V. Ledeneva explores practices in politics, business, media, and the legal sphere in Russia in the 1990s-from the hiring of firms to create negative publicity about one's competitors, to inventing novel schemes of tax evasion and engaging in "alternative" techniques of contract and law enforcement.Ledeneva discovers ingenuity, wit, and vigor in these activities and argues that they simultaneously support and subvert formal institutions. They enable corporations, the media, politicians, and businessmen to operate in the post-Soviet labyrinth of legal and practical constraints but consistently undermine the spirit, if not the letter, of the law. The "know-how" Ledeneva describes in this book continues to operate today and is crucial to understanding contemporary Russia.